Global citizenship education and the idea of diverse epistemologies - Horsthemke, Kai (Forum Pedagogiczne, 2020)
Three broad kinds of orientation can be identified with regard to (global) citizenship education (GCE): cosmopolitanism, localism, and relationalism. They differ in their respective approaches not only to cultural transmission and instruction but also to knowledge and knowledge production. My aim in this paper is to interrogate the notion of local or indigenous knowledge in GCE research and to investigate whether the postcolonial idea of diverse epistemologies does not employ a mistaken sense of ‘epistemology’. I argue that there are good reasons for an unequivocal and universally applicable understanding of knowledge and epistemology in (global) citizenship education and GCE research – and for being able to distinguish between knowledge and non-knowledge. Geographic, ethnic, racial and gender-based origin and affiliation do not constitute relevant criteria for any such demarcation. Instances in which they are cited as criteria raise questions not of epistemological relevance but rather of social justice.